Investigation of tribological properties of copper-fluoropolymer compositions and the development of a combined piston. - Дудчак, Т.В. (Problems of Tribology, 2015)
Dudchak T. V. Investigation of tribological properties of copper-fluoropolymer compositions and the development of a combined piston.The analysis of the influence of the clearance between the piston skirt and cylinder liners for the relining of the piston and the durability of parts of the internal combustion engine. One factor that affects the wear resistance and durability pairing: sleeve-ring-piston, this clearance is present between the bushing and the piston skirt, and the increase in his service. To ensure dimensi and even gap in coupling the piston and sleeve is one way of increasing the reliability and durability of the piston. When the large diametrical clearance between the piston skirt and liner, especially with a cold engine under the action of the gas forces normal and lateral force occurs relining of the piston, which is accompanied by punches him in the mirror of the sleeve. Relining is the cause of vibration, increased noise, fatigue and cavitation destruction of the parts. With the shifting of the piston leads to intensive wear of the liner, piston skirt, piston grooves, the ends of the piston rings. Proposed combined piston with inlays of copper-fluoropolymer compositions that will ensure the application of a thin film of copper on the surface of friction throughout the life of the internal combustion engine, which will greatly reduce scuffing, rubbing and increase the wear resistance of parts of the cylinder-piston group. Method of multifactorial experiment determined the optimal composition of the anti-friction composition.